Evaluation of a Multicomponent Tele-care Model for Supporting People with Prediabetes and Obesity in Chile - Pérez Ewert, J. Carola (2016)
Background: Prediabetes is a reversible condition and its treatment a chance to change unhealthy practices. Objective: to evaluate the effectiveness of a multi-component tele-care model to support people with pre-diabetes and obesity in Chile. Method: a randomized clinical trial in primary care setting, Santiago, Chile. Participants: 70 adults with pre-diabetes: BMI between 25 and 34 and access to mobile phone. GI (n = 33) received telephone counseling, SMS, educational materials and self-monitoring equipment and GC (n = 32) usual care and self-monitoring equipment. Measures of knowledge of prediabetes, unhealthy diet, physical activity, weight, waist circumference, glucose, triglycerides and total cholesterol were made pre and post intervention. Results: in GI the intervention to maintain stable knowledge level about pre-diabetes, and decrease triglycerides level was effective. The model did not exceed usual care for decrease in weight, waist circumference, glucose and cholesterol.